Excellent response of malignant peripheral nerve sheath tumour of retroperitoneum to radiation therapy. (17th December 2012) - Akhavan, Ali; Binesh, Fariba; Ghannadi, Fazlollah; Navabii, Hossein
Abstract : Malignant peripheral nerve sheath tumours are high-grade sarcomas originating from Schwann cells or nerve sheath cells. Most of these tumours are associated with major nerves of the body wall and extremities. The lower extremity and the retroperitoneum are the most common sites. Surgery is the cornerstone of treatment, however, radiation therapy is usually used as an adjuvant treatment. In this paper we present a 57-year-old Iranian woman with malignant peripheral nerve sheath tumour of retroperitoneum who was operated subtotally and then underwent radiation therapy which led to disappearance of all gross residual disease.